2005
DOI: 10.20886/ijfr.2005.2.2.75-88
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Three Polystyrene Impregnated Indonesian Wood Species

Abstract: Wood has long been recognized by the community, as the multi-purpose materials. In this regard, wood materials can be utilized for either construction, decoration, source of ~nergy, weapons, or other uses. Wood, as multi-purpose materials and considering its ~ssential existence, in its development has underwent a lot of modification. This fact is also spurred by some accompanying inconvenient situations, e.g. more difficulty in procuring wood, the· ever-increasing price of solid wood products, and less availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…The higher density wood had smaller voids that could be filled by the polystyrene. This result was in line with the findings of other researchers who reported that wood with a higher density had a lower weight percent gain of polystyrene polymer loading [9].…”
Section: Physical Propertiessupporting
confidence: 93%
See 4 more Smart Citations
“…The higher density wood had smaller voids that could be filled by the polystyrene. This result was in line with the findings of other researchers who reported that wood with a higher density had a lower weight percent gain of polystyrene polymer loading [9].…”
Section: Physical Propertiessupporting
confidence: 93%
“…Budiman et al [11] impregnated polystyrene into manii wood with the density of 370 kg/m 3 and obtained a polymer loading of 6.2%, which was 63% lower than our result. In contrast, Hadjib [9] used rubber-wood with a density of 510 kg/m 3 and got polymer loading of 26.9%, or more than twice our result. As shown in Table 1, wood species had a highly significant effect on weight percent gain due to polystyrene impregnation.…”
Section: Physical Propertiescontrasting
confidence: 58%
See 3 more Smart Citations